Understanding the Post-Lockdown Behavior of Learners: A Basis for Crafting a Child Protection Action Plan - de Guzman, Brian Joseph (Journal of Interdisciplinary Perspectives, 2025)
This study aims to understand post-lockdown learner misbehavior and its implications for child protection. Despite existing interventions, schools continue to report increasing cases of bullying, absenteeism, and disruptive behavior. Using a qualitative phenomenological approach, data were collected through face-to-face interviews with twenty selected informants, including school heads, teachers, parents, and learners. Findings revealed that while learners recognize their misbehavior, they lack awareness of its underlying causes, and parents struggle to explain it. Teachers play a crucial role in addressing these behavioral challenges, and school heads should develop intervention activities to help students cope with pandemic-related stress and anxiety. The study concludes that a structured child protection action plan is necessary to mitigate the long-term effects of post-pandemic stress on learner behavior.